2002
DOI: 10.4049/jimmunol.169.11.6435
|View full text |Cite
|
Sign up to set email alerts
|

A Potent and Selective Nonpeptide Antagonist of CXCR2 Inhibits Acute and Chronic Models of Arthritis in the Rabbit

Abstract: Much evidence implicates IL-8 as a major mediator of inflammation and joint destruction in rheumatoid arthritis. The effects of IL-8 and its related ligands are mediated via two receptors, CXCR1 and CXCR2. In the present study, we demonstrate that a potent and selective nonpeptide antagonist of human CXCR2 potently inhibits 125I-labeled human IL-8 binding to, and human IL-8-induced calcium mobilization mediated by, rabbit CXCR2 (IC50 = 40.5 and 7.7 nM, respectively), but not rabbit CXCR1 (IC50 = >1000 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(120 citation statements)
references
References 70 publications
(62 reference statements)
5
113
1
1
Order By: Relevance
“…The inflammatory process involves complex signaling cascades partly coordinated by chemokines, which recruit leukocytes, including large numbers of neutrophils, to sites of inflammation . Targeting chemokines with antibodies or binding proteins as well as targeting chemokine receptors has been attempted as a therapeutic strategy (Gong et al, 1997;Ogata et al, 1997;Plater-Zyberk et al, 1997;Barnes et al, 1998;Halloran et al, 1999;Matthys et al, 2001;Podolin et al, 2002;Yang et al, 2002) However, the overwhelming complexity of these signaling molecules (multiple chemokines, chemokine receptors, and redundancy) is a significant hurdle. Polychemokine (Carter, 2002) or combinations of different chemokine (al Mughales et al, 1996) antagonists have been suggested, but there may be chemokines that act as an agonist at one receptor and an antagonist at another (Xanthou et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory process involves complex signaling cascades partly coordinated by chemokines, which recruit leukocytes, including large numbers of neutrophils, to sites of inflammation . Targeting chemokines with antibodies or binding proteins as well as targeting chemokine receptors has been attempted as a therapeutic strategy (Gong et al, 1997;Ogata et al, 1997;Plater-Zyberk et al, 1997;Barnes et al, 1998;Halloran et al, 1999;Matthys et al, 2001;Podolin et al, 2002;Yang et al, 2002) However, the overwhelming complexity of these signaling molecules (multiple chemokines, chemokine receptors, and redundancy) is a significant hurdle. Polychemokine (Carter, 2002) or combinations of different chemokine (al Mughales et al, 1996) antagonists have been suggested, but there may be chemokines that act as an agonist at one receptor and an antagonist at another (Xanthou et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Therapies targeting CXCL2/CXCR2 have been tested in animal models of arthritis with concomitant reduction in neutrophil recruitment and TNF-a production (20), and immunization against CXCL2 was efficient in delaying the onset of arthritis and reducing the disease severity in a murine collagen-induced arthritis model (21). In addition, an antagonist of CXCR2 inhibited arthritis in rabbits (22). Our results imply that targeting CXCL2 as a strategy to treat RA would be beneficial in protection from bone destruction by directly inhibiting bone resorption, in addition to the already suggested antiinflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an antibody to IL-8/CXCL8 inhibited LPS-or monosodium urate crystal-induced leukocyte infiltration into rabbit knee joints (99,100). A nonpeptide oral antagonist of the IL-8/CXCL8 receptor, CXCR2, inhibited acute IL-8/CXCL8-or LPS-induced arthritis and chronic antigen (ovalbumen)-induced arthritis in rabbits (101). In LPS-induced rabbit arthritis, elevated SF GRO levels preceded knee joint leukocyte infiltration, which was inhibited 54% by GRO-specific neutralizing antibody, 48% by anti-IL-8, and 70% by a combination of both antibodies (102).…”
Section: Chemokine Targeting Strategies In Experimental Arthritismentioning
confidence: 99%